The other side of me - Sheldon, Sidney (New York : Warner Books, 2005)
"Memoir of entertainment legend Sidney Sheldon, now 88 years old, an Academy Award-winning screenwriter and creator of many television hits"--Provided by publisher.
Keywords: Sheldon, Sidney; Novelists, American -- 20th century -- Biography; Television writers -- United States -- Biography; Screenwriters -- United States -- Biography